Avtomatski varilski filter - Demšar, Andrej (Vakuumist, 2001)
Compared to the classic passive welding filter (darkened glass of plastic sheet), automatic LCD welding protection filter allows the welder undisturbed work without unnecessary lifting and lowering of the welding helmet. The automatic filter adjusts the light transmission according to the lighting condition, so that it darkens to the required shade level when welding light is detected and brightens when welding finishes. This result in more precise welding and increased productivity. Important performance of the automatic welding filter is that it provides full and permanent protection of the eyes against harmful IR and UV light, regardless of the transparency state. This protection is provided by vacuum deposited thin film layer interference filter which transmits a visible part of the spectrum and reflects UV and IR parts.
Keywords: varjenje; zaščita; varilski filtri; tekoči kristali